Like, follow, subscribe : influencer kids and the cost of a childhood online - Latifi, Fortesa (Gallery Books, 2026)
"A searing investigation into the child influencer industry and the perils of childhood internet fame, Like, Follow, Subscribe is essential reading for anyone seeking to understand the costs of internet fame, and the ethics of online content. What is it like to grow upwith a camera in your face 24/7? To have your childhood moments sold as "content" to millions online? What happens when someone who works in a largely unregulated multi-billion-dollar industry sells awaytheir childhood and has no financial safety net as an adult? What does it feel like to have your private moments-your medical diagnoses, your first period, your first break up, your tantrums, potty-training, and breastfeeding-weaning-broadcast to an audience of millions?Like, Follow, Subscribe shines a spotlight on the deeply troubling world of the child influencer industry. Journalist Fortesa Latifi dives into the lives of children whose parents mine their everyday activities for monetizable content, exposing issues like privacy violations, financial abuse, and the absence of child labor protections. Through expert interviews with psychologists, labor scientists, and even former child influencers and family vloggers, she uncovers the pressures, trauma, and consequences for children thrust into the spotlight. This timely and eye-opening book doesn't just reveal the harmof toxic social media culture: it also provides a roadmap to betterregulating influencer families, safeguarding children, and questioning the role of audiences in perpetuating these cycles of exploitation"--